Effects of education for sustainable development on personal norms regarding the scarcity of drinking water - Cruz, Thayse Santos da; Gomes, Sônia Maria da Silva; Figueiredo, Paulo Soares; Kouloukoui, Daniel; Cruz, Erisson Souza Barreto da (Revista de Administração da UFSM, 2022)
Purpose: This study aims to investigate effects of education for sustainable development (ESD) on university students' personal norms regarding the scarcity of drinking water in light of the value-belief-norm theory (VBN). Design/methodology/approach: The empirical research was developed at the Federal University of Bahia. The final sample was composed of 1,096 university students. The questionnaire was validated qualitatively and quantitatively. For hypothesis testing, Structural Equation Modeling was employed. Findings: Results indicated that the level of education for sustainable development positively impacted only biospheric values. The findings demonstrate that the impact of education for sustainable development depends on its quality, quantity, distribution, and diffusion in curricula. Research implications: This research is based on VBN theory and contributes to the body of literature of EDS. It suggests that individuals' values are in fact guiding principles of their beliefs. Practical implications: Biospheric values were found to have a positive effect on ecological beliefs. Nevertheless, it was found that in order to feel a moral obligation to act, students need to believe that, in fact, drinking water scarcity is a serious problem for society. Social implications: This research adds insights to the matter of educating the younger generation of students in view of the recent (2021-2022) water crisis in Brazil. Originality/value: The analysis of effects of "level of education for sustainable development” on individuals' values, impacting the VBN chain to explain student coping with drinking water scarcity is an original contribution of this study.